The Effectiveness of Healthy Romantic Relationship Training on Enhancing Active-Empathic Listening Skills Among Emerging Adults - Utami, Luh Ayu Candra; Ginanjar, Adriana Soekandar; Pranawati, Santy Yanuar (Bulletin of Counseling and Psychotherapy, 2024)
Active-empathic listening skills is one important factor in building healthy romantic relationship for emerging adults. Previous studies have focused more on sexual education, dating violence prevention, active listening, and empathic listening separately, without specifically targeting emerging adults. This study aimed to evaluate the effectiveness of healthy romantic relationship training on enhancing the active-empathic listening skills among emerging adults. The training included knowledge and skills related to active-empathic listening, such as knowledge about healthy romantic relationships, self-concept, adaptive coping strategy, and active-empathic listening skills. This study was conducted using a quasi-experimental within-subject design, measured using the Healthy Romantic Relationship Scale and the Active-Empathic Listening Scale (AELS). 13 unmarried emerging adults (M = 21.9) completed the training session until the follow-up session. Results from quantitative analysis using repeated measure ANOVA indicated that healthy romantic relationship training is effective on enhancing active-empathic listening skills in emerging adults (F(2,11) = 4.872, p = .031). Qualitative data further supported the hypothesis, showed the improvement in knowledge, skills, and confidence in applying active-empathic listening skills within future romantic relationships. Findings highlighted the importance of training programs focused on enhancing active-empathic listening skills to support emerging adults in achieving healthier outcomes in their romantic relationships